PLAYFUL BUILDING AND PROGRAMMING ROBOTS IN PRIMARY SCHOOLS - STOFFOVÁ, Veronika; ZBORAN, Martin (Trends in education, 2018)
This article is dedicated to an overview of robotic building kits which are being used in the education process at primary schools. The authors analyse, describe and propose the forms in which robot construction and programming can take place. They learn how the basic schools are equipped with robotic kits. The attitude of pupils towards the usage of the robotic building kit is being examined as well as evaluating the influence on their technical abilities, programming skills and knowledge in technical sciences. It describes the usage of robotic building kit LEGO MINDSTORMS EV3 in terms of assembling and programming process within the Informatics amateur club for 2nd degree level for primary school pupils.
Keywords: robot; robotic building kit; programming; Lego Mindstorms EV3